Characteristics of verbal fluency in patients with a primary episode of bipolar affective disorder - Mysula, Yuriy I. (Psychiatry, Neurology and Medical Psychology, 2020)
A study was conducted using the verbal fluency test of 153 patients with a primary episode of bipolar affective disorder: with prevalence of depressive symptoms (44 men and 75 women), with prevalence of manic symptoms (15 men and 8 women), and with simultaneous presence of depressive symptoms and manic symptoms phase change (6 men and 5 women).Significant impairment of test performance in patients with depression with respect to phonetic and semantic verbal fluency was revealed: the average number of words per letter "K" per 60 sec. in all patients 14,1±2,7 words, in men – 13,8±3,1 words, in women - 14,3±2,4 words, on the letter "P" – 12,5±2,8 respectively words, 12.3±3.2 words, 12.6±2.6 words, "Male Names" – 13.1±2.6 words respectively, 12.8±3.0 words, 13.3±2,4 words; "Fruits / furniture" – 12.0±2.4 words, 11.9±2.8 words, 12.1±2.1 words. Deterioration in the performance of semantic and phonemic verbal fluency test reflects the state of bradypsychism inherent in patients with depressive variant, which manifests a slow thinking rate, difficulty concentrating attention, motor inhibition, deterioration of operational capacity, rapid exhaustion. In patients with a maniacal variant, the high speed of the test is offset by a large number of errors due to the chaotic mental activity, instability and scattering of attention, the difficulty of maintaining focus of attention: the indicators were respectively 21.7±5.7 words, 22.5±5.7 words, 20,3±6.0 words; 20.3±5.6 words, 21.1±5.5 words, 19.0±5.9 words; 20.5±5.4 words, 21.2±5.2 words, 19.1±5.7 words; 19.5±5.4 words, 20.2±5.2 words, 18.1±5.7 words. In patients with mixed variants, the indicators of verbal fluency are reduced due to the influence of complex polymorphic symptoms with rapid change of state: respectively 16.5±5.6 words, 18.2±6.1 words, 14.4±4.8 words; 14.5±5.4 words, 16.2±5.7 words, 12.4±4.8 words; 15.4±5.4 words, 17.0±5.8 words, 13.4±4.8 words; 13.9±5.0 words, 15.5±5.3 words, 12.0±4.3 words. The differences in scores across all subtests in all groups between men and women are statistically insignificant (p>0.05).